Hubungan Antara Dukungan Sosial dengan Kecerdasan Emosi pada Mahasiswa di Universitas X Yogyakarta yang Menyusun Skripsi - Tyasdarmawan, Cantika Nursabrina; Ariyanto, Mustaqim Setyo; Fildzah Malahati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Students face various challengers when writing their theses, such as difficulty in meeting with their supervisors, finding literature books, and a lack of knowledge about research as well as difficulties in data analysis. Additionally, students often feel stressed during the thesis process, including the difficulty of determining the right theory, finding an appropriate title, and managing numerous revisions. With low emotional intelligence in facing the challenges of thesis writing and the lack of social support, students may struggle to cope with these issues. The purpose of this research is to determine the relationship between social support and emotional intelligence among students who are writing their theses at X University of Yogyakarta. The variables of social support and emotional intelligence were measured using a scale. The sample of this study consisted of 97 students at X University of Yogyakarta who were in the thesis writing stage. The data analysis test used in this research employed the Spearman Test method using Windows SPSS version 25. Based on the analysis of 97 students at X University of Yogyakarta revealed a correlation coefficient of 0.265 between social support and emotional intelligence, with a significant value of ρ = 0.009 (ρ < 0.05). Therefore, the research results indicate a significant relationship between social support and emotional intelligence. Students who receive higher social support tend to have better emotional intelligence, which positively affects their ability to manage stress and challenges during the thesis writing process.